Collagen biomaterial stimulates the production of extracellular vesicles containing microRNA‐21 and enhances the proangiogenic function of CD34+ cells. Issue 3 (7th December 2018) - Mcneill, Brian; Ostojic, Aleksandra; Rayner, Katey J.; Ruel, Marc; Suuronen, Erik J.
ABSTRACT: CD34 + cells are promising for revascularization therapy, but their clinical use is limited by low cell counts, poor engraftment, and reduced function after transplantation. In this study, a collagen type I biomaterial was used to expand and enhance the function of human peripheral blood CD34 + cells, and potential underlying mechanisms were examined. Compared to the fibronectin control substrate, biomaterial‐cultured CD34 + cells from healthy donors had enhanced proliferation, migration toward VEGF, angiogenic potential, and increased secretion of CD63 + CD81 + extracellular vesicles (EVs). In the biomaterial‐derived EVs, greater levels of the angiogenic microRNAs (miRs), miR‐21 and ‐210, were detected. Notably, biomaterial‐cultured CD34 + cells had reduced mRNA and protein levels of Sprouty (Spry)1, which is an miR‐21 target and negative regulator of endothelial cell proliferation and angiogenesis. Similar to the results of healthy donor cells, biomaterial culture increased miR‐21 and ‐210 expression in CD34 + cells from patients who underwent coronary artery bypass surgery, which also exhibited improved VEGF‐mediated migration and angiogenic capacity. Therefore, collagen biomaterial culture may be useful for expanding the number and enhancing the function of CD34 + cells in patients, possibly mediated through suppression of Spryl activity by EV‐derived miR‐21. These results may provide a strategy to enhance the therapeutic potency of CD34 + cells for vascular regeneration.—McNeill, B., Ostojic, A., Rayner, K. J., Ruel, M., Suuronen, E. J. Collagen biomaterial stimulates the production of extracellular vesicles containing microRNA‐21 and enhances the proangiogenic function of CD34 + cells. FASEB J. 33, 4166–4177 (2019). www.fasebj.org